OPTIMIZING NATIONAL DIGITAL TRANSFORMATION STRATEGIES: AN ADAPTED DESI FRAMEWORK FOR KAZAKHSTAN'S SOCIO-ECONOMIC GROWTH - Batyrbek, Bek; Khamitova, Ayauzhan; Bekzhan, Adilet; Askerova, Sara (Nazarbayev University School of Engineering and Digital Sciences, 2024)
The project aims to assess the Digital Economy and Society Index (DESI) for Kazakhstan by implementing a benchmark of the European Commission developed for EU countries. The index is composed of dimensions, sub-dimensions, and indicators that summarize the digital performance of the countries. The framework was applied for Kazakhstan to effectively evaluate the digital transformation level and further track potential growth in the digitalization process of the country. The project discusses the key dimensions of DESI, namely Human Capital, Digital Public Services, Integration of Digital Technologies, and Digital Infrastructure. Each of the dimensions’ indicators was extracted from both secondary and primary research methods. The official websites of e-Gov, the National Bureau of Statistics, statGov, and the Ministry of Digital Development, Innovations, and Aerospace Industry were investigated to provide relevant data for the final DESI calculation. To evaluate the extent of the adoption of digital technologies among enterprises, a survey was conducted among SMEs and large enterprises based in Kazakhstan. The comparative analysis was executed to analyze which indicators outperformed and which ones require extensive research to support the digital transformation of Kazakhstan. Additional recommendations were provided in the form of new indicators that need further exploration to precisely assess the country’s digital economy and performance.
Keywords: type of access: embargo; digital transformation; digitalization; information and communication technologies; digital economy; society